Pengembangan panduan bimbingan kelompok dengan menggunakan teknik homeroom untuk meningkatkan self-control siswa di sekolah menengah pertama - Siboro, Yogi Martogi; Gading, I Ketut; Dharmayanti, Putu Ari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This research aimed to develop a group guidance guidebook using self-control techniques aimed at increasing self-control in seventh grade junior high school students.This research belongs to the developmental research type with the 4D development procedure (Define, Design, Develop, and Disseminate). Three experts and two counseling practitioners were involved in this study to test the acceptability of the guidance book. Research data was collected through a questionnaire and analyzed using Content Validity Ratio (CVR), Content Validity Index (CVI), Cronbach's Alpha, and t-test formulas. The CVR analysis results showed that all questionnaire items were accepted and obtained a CVI score of 1 with a very good category, which means that the guidance book for self-control group counseling with the teacher technique met the acceptability requirements. The effectiveness of the guidance book was tested on 10 students from 7th grade at SMP Negeri 6 Singaraja using a one-group pre-test post-test experimental design. The t-test results showed a significance value of 0.002, which means that the use of the self-control group counseling guidance book with the teacher technique is effective in enhancing self-control among 7th grade junior high school students.